Uji Repelensi Minyak Atsiri Serai Wangi dan Ekstrak Daun Mimba Terhadap Hama Gudang Corcyra cephalonica - Muhayati Rofiah; Nanang Tri Haryadi (Universitas Merdeka Madiun, 2024)
Corcyra cephalonica is storage insect pest that are polyphagous. (Cymbopogon nardus L.) is a plant from the Gramineae group that produces essential oils. Useful as an insect repellent. In addition to the use of citronella, the pest attack of Corcyra cephalonica can be overcome with neem leaf extract. Neem is a plant that contains ingredients that can overcome pests on plants. This research was conducted to find out the test of repellency of citronella essential oil and neem leaf extract on repellent of Corcyra cephalonica by knowing the right concentration in biological pest management applications. The study used the basic pattern of non-factorial RAL. Used a dual-choice method. Treatment, (A1) : 10% citronella oil (A2) : 15% citronella oil (B1) : 10% neem extract (B2) : 15% neem extract. the results of the research that have been obtained, it can be concluded that the response of citronella essential oil and neem leaf extract to the rejection of Corcyra cephalonica at the larval stage were significantly different. The repellent of citronella essential oil and neem leaf extract of the imago stage were very significantly different. The highest percentage of imago repellency was in the 15% neem leaf extract treatment.